On the origin of the electron blocking effect by an n-type AlGaN electron blocking layer - Zhang, Zi-Hui (2014)
In this work, the origin of electron blocking effect of n-type Al0.25Ga0.75N electron blocking layer (EBL) for c+ InGaN/GaN light-emitting diodes has been investigated through dual-wavelength emission method. It is found that the strong polarization induced electric field within the n-EBL reduces the thermal velocity and correspondingly the mean free path of the hot electrons. As a result, the electron capture efficiency of the multiple quantum wells is enhanced, which significantly reduces the electron overflow from the active region and increases the radiative recombination rate with holes.